1991
DOI: 10.3168/jds.s0022-0302(91)78329-x
|View full text |Cite
|
Sign up to set email alerts
|

Changing Dietary Electrolyte Balance for Dairy Cows in Cool and Hot Environments

Abstract: Two Latin square studies, each containing eight primiparous cows (four Holstein, four Jersey), were conducted to determine the effect of changing dietary electrolyte balance during cool and hot environmental conditions on performance of lactating dairy cows. Electrolyte balance, expressed as Na + K - Cl in milliequivalents per kilogram of diet, was altered by changing K and Cl content in the diet using potassium bicarbonate or calcium chloride. Maximum and minimum temperatures averaged 26.7 and 15.0 degrees C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
73
5
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(131 citation statements)
references
References 11 publications
36
73
5
5
Order By: Relevance
“…Similar results were also reported by West et al (1991 and, which observed that urinary cation-anion difference was increased with DCAD increase. Hu and Murphy (2004) described that urinary concentrations of K and Cl linearly increased as its respective dietary concentrations were increased, whereas urinary Na concentration rose in a quadratic form according to the level of this mineral in the diet.…”
Section: Blood Metabolismsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar results were also reported by West et al (1991 and, which observed that urinary cation-anion difference was increased with DCAD increase. Hu and Murphy (2004) described that urinary concentrations of K and Cl linearly increased as its respective dietary concentrations were increased, whereas urinary Na concentration rose in a quadratic form according to the level of this mineral in the diet.…”
Section: Blood Metabolismsupporting
confidence: 90%
“…In contrast, Fredeen et al (1988) described that blood concentration of Na was reduced with DCAD reduction. Other studies, Tucker et al (1988);West et al (1991) and Marques et al (2011), did not observe effect of DCAD on blood concentrations of Na and K. Therefore, there are different results about the effect of DCAD on blood concentrations of Na and K; which may be due to the different methodologies that were used to study DCAD, as following: type of anionic or cationic salt used; DCAD levels studied; type of diets (TMR or concentrate supplementation of dairy cows grazing pasture, as well as forage : concentrate ratio) and mineral concentration of diets evaluated.…”
Section: Blood Metabolismmentioning
confidence: 86%
See 1 more Smart Citation
“…West et al (1991); Joyce et al (1997) A concentração de Na no sangue é mantida relativamente constante por meio da regulação do consumo e excreção do elemento (Swenson, 1984). Uma possível explicação para os resultados obtidos seria a resposta compensatória dos rins, ou seja, conforme o BCAD aumentou, com consequente aumento da ingestão de Na, pode ter ocorrido maior excreção urinária desse mineral, mantendo sua concentração no sangue.…”
Section: Resultsunclassified
“…In principle, corrections in blood acid-base balance and associated electrolyte losses may be achieved through modification of the DCAD. Diets formulated with DCAD of 250 mEq/kg DM have been recommended for optimal growth in chickens (Mongin 1981) and pigs (Austic and Calved 1981;Patience et al 1987), and 200-370 mEq/kg DM for optimal milk yield in lactating dairy cattle West et al 1991). The DCAD is usually manipulated by the addition of weak buffers such as NaHCO 3 , KHCO 3 and K 2 CO 3 .…”
Section: Introductionmentioning
confidence: 99%